Considerations for the Surgical Management of Thoracic Cancers During the COVID-19 Pandemic: Rational Strategies for Thoracic Surgeons - Zhang, Jiahao; Han, Yichao; Zhang, Yajie; Dong, Dong; Cao, Yuqin; Chen, Xiang; Li, Hecheng (Frontiers in Surgery, 2022)
Objective: The novel coronavirus disease 2019 (COVID-19) has resulted in a global health crisis since first being identified in December 2019. As the pandemic continues to strain global public health systems, elective surgeries for thoracic cancer such as early-stage lung cancer and esophageal cancer have been postponed due to shortage of medical resources and risk of nosocomial transmission. This review aimed to discuss the influence of COVID-19 on thoracic surgical practice, prevention of nosocomial transmission during the pandemic, and propose modifications to the standard practices in surgical management of different thoracic cancer. Methods: A literature search of the PubMed, Medline, Google Scholar was performed for articles focusing on COVID-19, early-stage lung cancer and esophageal cancer prior to July 1, 2021. The evidence from articles was combined with our data and experience. Results: We review the challenges in the management of different thoracic cancer from the perspectives of thoracic surgeons and propose rational strategies for the diagnosis and treatment of early-stage lung cancer and esophageal cancer during the COVID-19 pandemic. Conclusions: During the COVID-19 pandemic, the optimization of hospital systems and medical resources is to fight against COVID-19. More indolent lung tumors such as pure ground glass tumors, can likely be postponed, while selective surgeries of more biologically aggressive tumors should be prioritized. As for esophageal cancer, immediate surgery for esophageal cancer stage Ib or greater and esophageal cancer after neoadjuvant therapy is recommend. Preoperative screening for COVID-19 should be performed routinely prior to thoracic surgeries. Prevention of nosocomial transmission with propriate personal protective equipment including N-95 respirator masks with eye protection is necessary.